Coupling hierarchical iron cobalt selenide arrays with N-doped carbon as advanced anodes for sodium ion storage. Issue 11 (26th February 2021) - Wang, Peijia; Huang, Jiajie; Zhang, Jing; Wang, Liang; Sun, Peiheng; Yang, Yefeng; Yao, Zhujun
Abstract : Hierarchically core–branched iron cobalt selenide arrays coated with N-doped carbon shell were designed and synthesized on carbon cloth, showing prominent electrochemical performance both in half-cell and full cell sodium ion batteries. Abstract : Transition metal selenides have emerged as a class of promising anodes for sodium ion batteries (SIBs). However, the notorious issues of their low electrical conductivity and huge volume changes during sodium ion insertion/extraction lead to poor cycling stability and inferior rate capability. In this work, hierarchically core–branched iron cobalt selenide arrays coated with N-doped carbon shell (denoted as FeCo–Se@NC) were rationally designed and synthesized on carbon cloth through a combined strategy of hydrothermal, selenization and carbonization processes. Benefitting from the designed arrays with simultaneous Fe doping into the CoSe2 matrix and N-doped carbon coating, the optimized FeCo–Se@NC electrode possesses greatly enhanced structural integrity and accelerated ion/electron transfer kinetics. When employed as a binder- and additive-free anode for SIBs, the FeCo–Se@NC electrode exhibits a high reversible capacity of 532.1 mA h g −1 at 0.05 A g −1, competitive rate capability (193.3 mA h g −1 at 5 A g −1 ), and good cycling stability (386.1 mA h g −1 after 150 cycles at 0.5 A g −1 ). Moreover, when coupled with Na3 V2 (PO4 )3 /C, the full cell delivers a high capacity of 350.6 mA h g −1 at 0.1 A g −1 and a high energy density of 276.7 W h kg −1 . This work is expected to provide a new avenue for the development of arrayed transition metal selenide-based materials for high-performance SIBs.